Persatuan Islam dan Sosio Kultural Masyarakat Lampung Utara - Adilan, Dilan Imam (Al-Adyan: Journal of Religious Studies, 2020)
The focus of this research is on the people of Talang Harapan, Kotabumi, North Lampung, whose cultural life and religious understanding are still tied to the traditions of their ancestors. Their religious understandings have been experiencing friction with da'wah movement of Islamic Union (Persatuan Islam; PERSIS) which is critical of occultism and local traditions, especially talking about the mixing of culture and religion.  Through a new ethnographic method based on qualitative descriptive method, this study shows an alternative da'wah of Islamic Union that utilizes the "development of religion of bil hal" by providing free health services of cupping therapy  that becomes a new medium for community's acceptance towards the presence of PERSIS da'wah.Fokus penelitian ini pada masyarakat Talang Harapan, Kotabumi Lampung Utara yang budaya kehidupan dan pemahaman keagamaannya masih terikat dengan tradisi nenek moyang. Pemahaman keagamaan masyarakat Talang Harapan ini mengalami gesekan dengan gerakan dakwah Persatuan Islam (PERSIS) yang kritis terhadap praktik okultisme dan tradisi lokal, khususnya berbicara tentang percampuran budaya dan agama. Melalui metode etnografi baru yang berbasis deskriptif kualitatif, penelitian ini menunjukkan dakwah alternatif PERSIS yang mengambil pendekatan “pengembangan  agama bil hal” dengan memberikan pelayanan kesehatan terapi bekam gratis menjadi suatu media baru penerimaan masyarakat Talang Harapan terhadap kehadiran dakwah PERSIS.